Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.ejvs.2019.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Closure and the Risk of Incisional Hernia in Aneurysm Surgery – A Systematic Review and Meta-analysis

Abstract: WHAT THIS PAPER ADDSThe prevalence of incisional hernias after open abdominal aortic aneurysm repair is high, up to 36 % in some analyses. Several studies exist regarding techniques and considerations to be taken in order to reduce the risk of this post-operative complication. This systematic review and meta-analysis collates these data and reemphasizes the reduced risk associated with mesh-augmentation, when using a vertical midline incision. Finally, a suture to wound ratio of more than 4:1 is associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 35 publications
0
16
1
Order By: Relevance
“…Furthermore, patients operated for an AAA are usually older than patients operated for other aortoiliac vascular diseases. [ 4 , 6 , 9 ] In our study, the mean age was 70.1±10.1 in the AOD group and 68.7±9.6 in the AAA group, indicating no statistically significant difference. Some authors have noted a risk factor for male sex incisional hernia.…”
Section: Discussionmentioning
confidence: 46%
See 4 more Smart Citations
“…Furthermore, patients operated for an AAA are usually older than patients operated for other aortoiliac vascular diseases. [ 4 , 6 , 9 ] In our study, the mean age was 70.1±10.1 in the AOD group and 68.7±9.6 in the AAA group, indicating no statistically significant difference. Some authors have noted a risk factor for male sex incisional hernia.…”
Section: Discussionmentioning
confidence: 46%
“…[ 14 ] However, some studies have reported no significant difference between the incision type and hernia. [ 6 , 15 ] According to a recent systematic review, five studies compared transverse with midline incisions in a total of 3,399 patients (2,098 with transverse and 1,301 midline incisions). [ 6 ] There was a trend toward a benefit of transverse incisions, but the results were not significant (p=0.08).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations